Analisis dan Peningkatan Keamanan Objek Vital, Pengamanan File dan Pengamanan Cyber di PT. Prudential Life Assurance (International Forum of Researchers and Lecturers, 2023)
In the digital era that continues to grow, PT Prudential Life Assurance as an insurance company must face increasingly complex security challenges. As one of the leading companies in the insurance industry, PT Prudential Life Assurance manages vital objects, such as customer data, financial information, and network systems that are crucial to maintain smooth operations. In this context, security of vital objects, file security, and cyber security are key factors that must be taken seriously. This research was conducted online using sources that can be accessed via the internet, such as articles and related sources available on Google. Therefore, there is no specific physical location that is the focus of this research. Based on the research conducted, it was found that PT Prudential Life Assurance has a comprehensive approach in maintaining the security of their vital objects. File Security In terms of file security, PT Prudential Life Assurance uses a sophisticated and encrypted file management system to protect important data and documents. Cyber Security In an effort to maintain cyber security, PT Prudential Life Assurance has taken important steps. It can be concluded that, PT Prudential Life Assurance has implemented comprehensive security measures to protect the company's vital objects. Its security has proven effective through the use of an encrypted file management system and strict access policies. The company has also implemented important steps in cyber security, including strict IT security policies, threat monitoring, and preventive measures against malware and DDoS attacks.